IMPLEMENTASI METODE SINGLE MINUTE EXCHANGE OF DIES (SMED) SEDERHANA UNTUK MEREDUKSI PROSES SETUP CLEAN UP DI LINE MESIN COATING SALUT GULA - Rifael Satrio Adinugroho; Dian Adriani; Tyara Rossalina; Dede Suhendar (Journal Prima Health Science, 2020)
The setup clean-up process needs much work time, and this is not good news for a pharmaceuatical company.It will extend downtime, resulting in delays in the production area. Companies must be able to fix thisproblem by minimizing clean-up setup time and process time. The purpose of this study is to minimize thesetup clean up time at the sugar-coated coating line machine using the SMED (Single Minute of ExchangeDies) approach. The research method used is time study and then doing some classification, conversion, andsimplification of this process. The result is that the setup clean up time has dropped significantly at theaverage by 28%. A more concise and efficient process will have a positive effect on the production processlead-time. In addition to these positive results, companies will get benefit from getting new workflows thatare leaner. Of course, this process needs to be validated in order to get excellent and consistent final results